STAD Co-operative Model: An Effort to Improve Learning Outcomes of Subtraction and Addition of Fractions - Indah Shofiatin, Indah Shofiatin; Miristianti, Cindy Nur; Faqih, Mohammad Iqbal; Kusnandar, Qayla Firdhausa Restu (Journal of Action Research in Education, 2024)
This research is motivated by the previous learning habits of fifth grade students of SDN Gili Barat, namely students are accustomed to learning in classical classes and teacher-centred learning strategies that emphasise teacher-centred learning, causing students' potential and abilities not to be maximally activated. The purpose of this study based on the existing problems is to improve the learning outcomes of Mathematics about adding and subtracting various forms of fractions through the STAD type cooperative learning model for grade V students of SDN Gili Barat Bangkalan. The subjects of this study were 23 grade V elementary school students. Implementation of class action research in class VB SDN Gili Barat in the 2023/2024 academic year, carried out in II cycles, each cycle through 4 stages, including: Planning, implementation, data collection, and reflection. Student learning outcomes improved from cycle I to cycle II learning. Thus, the STAD type cooperative learning model can improve the learning outcomes of grade V students at SDN Gili Barat Bangkalan.